Products for Human Consumption from Antarctic Krill - Joseph, Jose; V., Muraleedharan; R., Thankamma; C.N., Ravishankar (Fishery Technology, 2025)
Studies were conducted to formulate different products using frozen-stored whole krill/krill meat. Dried krill of good quality could be prepared by blanching krill in boiling 5% salt solution for 5 min and then sun drying. Incorporation of krill mince even at a level of 10% to Catla catla mince for production of mixed mince and fish paste adversely affected the quality. Though a prawn like flavour was imparted on mixing krill mince with Catla catla mince during preparation of fish cutlet and fish burger, it gave a bitter after taste at 10% level and bitter taste at 20% level or above. The swelling property of the fish wafers was affected by incorporation of krill mince.